EPIDEMIOLOGICAL AND CLINICAL CHARACTERISTICS OF HIDRADENITIS SUPPURATIVA PATIENTS: 10-YEAR EXPERIENCE FROM A SINGLE TERTIARY CENTER - Selda Işık Mermutlu; Zeynep Keskinkaya (İstanbul Tıp Fakültesi Dergisi)
Objective: To investigate the clinico-epidemiological profile of hidradenitis suppurativa (HS) patients.Material and Method: In this retrospective cross-sectional single tertiary center study, the HS patients diagnosed and/or followed up between 2012-2022 were evaluated regarding demographic features, clinical findings, associated comorbidities, therapies initiated for HS and their outcomes.Results: Of 101 HS patients (male:female ratio=1.7:1), 23.3% (n=20) had a history of early-onset disease (<18 years). The majority had no family history of HS (82.7%, n=62). The patients were classified according to disease severity as Hurley I (33.7%, n=34), Hurley II (46.5%, n=47) and Hurley III (19.8%, n=20). Patients with early-onset disease and Hurley III HS had a significantly higher number of affected anatomical sites (p<0.05). The axillary region was the most commonly involved anatomical site (n=78), followed by the inguinal (n=57) and gluteal regions (n=23).Sixty-four patients (74.4%) were overweight/obese, and 84.5% (n=71) were current or ex-smokers. Acne vulgaris was the main dermatological comorbidity associated with HS (n=23). Pilonidal sinus disease was present in 25.5% (n=25). Patients with Hurley III HS presented with significantly higher rates of pilonidal sinus disease and involvement of the gluteal and perianal regions (p<0.05). Nineteen patients were diagnosed with metabolic syndrome. Systemic antibiotics were the most frequently prescribed first-line agents. Hidradenitis Suppurativa Clinical Response (HiSCR) achievement was observed most frequently with biologics, particularly adalimumab.Conclusion: In line with the current literature, HS poses an increased disease burden with its associated comorbidities. The predominance of the male sex and the anatomical involvement patterns seen in our HS patients are compatible with previously reported Turkish series. Pilonidal sinus disease and involvement of the gluteal and perianal regions in HS patients are important signs of severe disease, also highlighted in recent studies. The biologic agents seem to be the best therapeutic option for achieving HiSCR, especially in severe HS forms.